2019
DOI: 10.3389/fnins.2019.00401
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuitry Underlying Waking Up to Hypercapnia

Abstract: Obstructive sleep apnea is a sleep and breathing disorder, in which, patients suffer from cycles of atonia of airway dilator muscles during sleep, resulting in airway collapse, followed by brief arousals that help re-establish the airway patency. These repetitive arousals which can occur hundreds of times during the course of a night are the cause of the sleep-disruption, which in turn causes cognitive impairment as well as cardiovascular and metabolic morbidities. To prevent this potential outcome, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 110 publications
1
67
0
Order By: Relevance
“…These projections are important in the coordinated control of the upper airways with breathing during orofacial behaviors involving similar anatomical pathways, such as swallowing, cough, and vocalizations (Bautista, Fong, & Dutschmann, 2014; Browaldh et al., 2016; Jakus et al., 2008). Additionally, through connections with regions mediating the arousal component of hypoxic/hypercapnic chemoreflexes, the KF may also play a role in the state‐dependent adjustments of respiratory rate and pattern (Kaur & Saper, 2019). For instance, the KF receives chemosensory information from the lateral hypothalamus, retrotrapezoid nucleus (RTN), medullary raphe, the nucleus of the solitary tract (NTS), and the locus coeruleus (LC) (Guyenet & Bayliss, 2015; Hancock & Fougerousse, 1976; Herbert, Moga, & Saper, 1990; Kaur & Saper, 2019; Peyron et al., 1998; Robertson, Plummer, Marchena, & De, 2013; Yokota, Oka, Asano, & Yasui, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These projections are important in the coordinated control of the upper airways with breathing during orofacial behaviors involving similar anatomical pathways, such as swallowing, cough, and vocalizations (Bautista, Fong, & Dutschmann, 2014; Browaldh et al., 2016; Jakus et al., 2008). Additionally, through connections with regions mediating the arousal component of hypoxic/hypercapnic chemoreflexes, the KF may also play a role in the state‐dependent adjustments of respiratory rate and pattern (Kaur & Saper, 2019). For instance, the KF receives chemosensory information from the lateral hypothalamus, retrotrapezoid nucleus (RTN), medullary raphe, the nucleus of the solitary tract (NTS), and the locus coeruleus (LC) (Guyenet & Bayliss, 2015; Hancock & Fougerousse, 1976; Herbert, Moga, & Saper, 1990; Kaur & Saper, 2019; Peyron et al., 1998; Robertson, Plummer, Marchena, & De, 2013; Yokota, Oka, Asano, & Yasui, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The BF is considered the final node of the ventral arm of the ARAS, since it receives input from multiple arousal systems in the brainstem and hypothalamus and contains several neurotransmitter systems with projections to the cortex (Jones, 2003;Zaborszky et al, 2012;Brown et al, 2012;Lin et al, 2015;Yang et al, 2017). Recent studies demonstrated that brainstem parabrachial nucleus glutamatergic neurons relay signals about blood carbon dioxide (CO2) levels and mediate arousals from sleep in response to hypercarbia (excessive CO2) Kaur and Saper 2019). These neurons project to the BF, and optogenetic inhibition of their terminals in the BF markedly delayed arousal from sleep in response to hypercarbia (Kaur 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, GABAergic neurons in the medullary parafacial zone located in the brain stem and the ventral tegmental area (7) and adenosine expressing neurons in the nucleus accumbens are involved in the regulation of rapid eye movement (REM) sleep, whereas the MT2 receptors selectively increase non-REM sleep (8). While the POA contains not only sleep-promoting neurons but also wake-promoting neurons (9), noradrenergic neurons in the locus coeruleus, serotonergic neurons in the dorsal raphe, and histaminergic neurons in the tuberomammillary nucleus are only implicated in regulation of wakefulness (10). Orexin/hypocretin neurons in the lateral hypothalamus play a crucial role to maintain wakefulness by orchestrating the activity of these monoaminergic neurons (11).…”
Section: Sleep / Wake Cycle In Non-intensive and Intensive Care Unitmentioning
confidence: 99%